Efficacy of Co-Crystal of Tramadol-Celecoxib (CTC) in Patients with Acute Moderate-to-Severe Pain: A Pooled Analysis of Data from Two Phase 3 Randomized Clinical Trials - Richard Langford; Eugene R. Viscusi; Adelaida Morte; Jesús Cebrecos; Mariano Sust; José María Giménez-Arnau; Oscar de Leon-Casasola (Adis, Springer Healthcare, 2024)
Abstract Background and Objectives New acute pain medications are needed that provide effective analgesia while minimizing side effects and opioid exposure. Clinical trials of co-crystal of tramadol-celecoxib (CTC) have demonstrated an improved benefit/risk profile versus tramadol or celecoxib alone. We pooled data from two phase 3 clinical trials to evaluate the efficacy of CTC 200 mg twice daily (BID) in acute moderate-to-severe pain. Methods Efficacy data were pooled from STARDOM1 [acute pain following oral surgery (NCT02982161)] and ESTEVE-SUSA-301 [acute pain following bunionectomy (NCT03108482)]. The primary efficacy outcome was sum of pain intensity difference from 0 to 48 h (SPID0-48). Results A total of 344 patients received CTC 200 mg BID, 342 received tramadol 50 or 100 mg four times a day, 181 received celecoxib 100 mg BID, and 172 received placebo. The least-squares mean difference in SPID0-48 was −21.8 (p = 0.002) for CTC versus tramadol and −72.8 (p < 0.001) for CTC versus placebo. A similar pattern of SPID0-48 was observed with CTC versus comparator whether patients had moderate or severe pain at baseline. Reduction in pain intensity was faster and reached mild intensity earlier with CTC versus comparators. Patients were significantly (p ≤ 0.005) less likely to receive rescue medication within 4 or 48 h with CTC compared with tramadol or placebo. Conclusions This pooled analysis reinforces the efficacy profile of CTC versus tramadol and, given that CTC permits lower daily tramadol dosing and thereby reduces unnecessary opioid use, this highlights its improved benefit/risk profile and its potential for the management of moderate-to-severe pain.